Indonesian Students’ Mathematical Literacy And Attitude - Karolina, Venny; Ulfah, Maria; Queiroz, Carla (International Journal of Educational Research & Social Sciences, 2022)
This study aimed to analyze gender differences in mathematical literacy and attitude among secondary school students in Indonesia. This study also assessed the correlation between mathematical literacy and attitude. Secondary data set of PISA Mathematic 2012 was used in this study. The participants of the survey were 5622 Indonesian secondary school students (2860 females and 2762 males). The findings of this study were as follows. Firstly, the study found evidence that compared to females (m=22.6%), male students (m=23.2%) had significantly higher scores in mathematical literacy (p  0.001, t = -1.630, df = 5542.617). Secondly. there was no difference between male (m=3.07) and female students (m=3.06) in mathematical attitude (p = 0.73, t = 0.431, df = 3716). Lastly, this study found that there were no linear correlations between mathematical literacy and attitude (p = 0.982, r < 0.001).